FANGAOID GOT ACQUAINTED WITH ALL THE ACTIVITIES BASED ON WHAT A PROJECT (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The article presents examples of the transformation of tasks based on the application of science knowledge from physics to competence-oriented tasks.